Vitamin D status in sarcoidosis: a cross-sectional study - Papanikolaou, Ilias C; Tabila, Brian; Tabila, Kristina; Borok, Zea; Sharma, Om P; Gould, Michael K (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2018)
Background: Hypercalcemia, a common feature in sarcoidosis, is due to the excessive production of active Vitamin D metabolite, 1,25(OH)2D. Levels of 25(OH) Vitamin D however may not be appropriate. Objectives: To assess Vitamin D status and its clinical associations in sarcoidosis patients compared to a general respiratory diseases out-patient clinic population, serving as controls. Methods: 64 sarcoidosis cases and 53 control cases with other than sarcoidosis respiratory diseases, matched for age and sex were included in the study. Serum 25(OH)D, 1,25(OH)2D, calcium, angiotensin converting enzyme (ACE) were measured. 25(OH) Vitamin D was described as deficient when <20 ng/ml and insufficient when <30 ng/ml. Clinical parameters were recorded for sarcoidosis cases. Results: Overall 41/64 sarcoidosis cases (64%) had low 25(OH) D, 7/64 (11%) had high 1,25(OH)2D and 2/64 had hypercalcaemia (3%). Sarcoidosis subjects likely exhibited deficient (39%) or normal 25(OH)D levels (36%) in comparison to controls (p=0.018). 25(OH) Vitamin D deficiency in sarcoidosis was associated with race and radiological stage I disease, with regression analysis identifying African-American race as the only significant risk factor (p=0.03). An inverse correlation between ACE and 25(OH)D levels was found (p=0.052). 1,25(OH)2D was significantly elevated in sarcoidosis compared to controls. Among sarcoidosis patients, those with insufficient 25(OH)D levels exhibited higher calcium levels in serum. Conclusions: 25(OH) Vitamin D deficiency is prevalent in sarcoidosis, particularly in African-Americans and likely those with active disease. However, concomitant 1,25(OH)2D elevation and associated hypercalcaemia make Vitamin D supplementation dangerous in sarcoidosis.